2020
DOI: 10.14218/jcth.2020.00076
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Infections in Cirrhotic Patients in a Tertiary Care Hospital

Abstract: Background and Aims Patients with cirrhosis are immunocompromised and at higher risk of developing infections compared to the general population. The aim of this study was to assess the incidence of infections in cirrhotic patients in a large academic liver center and investigate potential associations between infections, bacteria isolated, therapeutic regimens used, and mortality. Methods This was a retrospective chart review study, including 192 patients. All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Furthermore, in contrast with the study of Lingiah and al. [ 25 ], showing a higher incidence of infections, we excluded asymptomatic bacteriuria and bacterascites from the main analysis, as our SAVE guidelines do not recommend antibiotic therapy for them, in line with other similar guidelines (except for clinical features suggestive for infection) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in contrast with the study of Lingiah and al. [ 25 ], showing a higher incidence of infections, we excluded asymptomatic bacteriuria and bacterascites from the main analysis, as our SAVE guidelines do not recommend antibiotic therapy for them, in line with other similar guidelines (except for clinical features suggestive for infection) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular the study of Lingiah and al. [ 25 ] considered in the same group asymptomatic and symptomatic infections all together.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter retention time of urinary catheters, nasogastric tubes and intra-abdominal drains could reduce some related postoperative complications. Indwelling urinary catheters can increase the risk of postoperative lung and urinary tract infections ( 20 ), and indwelling nasogastric tubes contribute to a high risk of lung infection in patients ( 21 ), which further delays patient recovery. Moreover, a multicentre RCT showed that the absence of an intra-abdominal drain after OPD significantly increased the incidence of complications and mortality by 4 fold ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, positive culture results are observed in 17%-28% of patients with liver cirrhosis accompanied by pulmonary bacterial infections, with gram-positive cocci (GPC) the predominant causative agents of CAP in liver cirrhosis (75%), 6,11,22 while approximately 4.8% of patients show negative culture results, even with positive imaging. 5 Table 1 lists the pathogens in CAP and HAP among cirrhotic patients. Among gram-positive bacteria, the most commonly isolated are Streptococcus pneumoniae, followed by Staphylococcus aureus and other Streptococcus species.…”
Section: Capmentioning
confidence: 99%
“…[1][2][3] Complications of decompensated cirrhosis include ascites, gastroesophageal variceal hemorrhage, sepsis, hepatic encephalopathy and hepatorenal syndrome. 4 Patients with liver cirrhosis are more susceptible to bacterial infections than the general population, 5 with 25%-50% of cirrhotic inpatients developing bacterial infections. 6 Cirrhotic patients with bacterial infections are more susceptible to decompensation and have a higher likelihood of mortality.…”
Section: Introductionmentioning
confidence: 99%